History of music - Sweet, Bertha Florence (My University, 1907)
Introduction: Rome has almost all the credit for the early development of music, but according to actual history it seems that the Romans were a people of observance of and appreciation for arts, but the artists were all from foreign countries, who came to Rome to receive the praise of the hosts, and then made their homes there, practicing and teaching. The most ancient treatise on music is written in the Grecian language, and there had been no original work on the subject by the Romans till the time of Boethius. Another cause for Rome becoming the center of music is that of the spread of the Christian religion. The persecution of the Christians in their own countries caused many to flee from their mother land, and seek the lad of Rome, where they could worship in secrecy. With them they brought the memory of the songs of their native land, and by an intermingling of the various melodies of the different countries, a new type of music was created, but even this deteriorated, as there was no written music, and the so-called melodies were either changed or forgotten.
Citation: Sweet, Bertha Florence. History of music. Senior thesis, Kansas State Agricultural College, 1907.
Morse Department of Special Collections
Keywords: History of Music; Cultural Influences on Music; Political Influences on Music; Theses